ANALISIS SISTEM PEMBIAYAAN PERUMAHAN SYARIAH TANPA BANK MENURUT FATWA DSN MUI - Arifah Nuriyah Kaka Jodho (JURNAL ILMIAH EDUNOMIKA, 2024)
Research Objective: Analyse the risk of late payment on sharia housing "Rumahku Surgaku. Analysing the financing process with a focus on the murabahah aspect of Islamic housing "My Heavenly Home. Analysing the implementation of Fatwa DSN MUI in the bankless Islamic housing system. Research Methodology: The research used a descriptive qualitative approach with direct interviews. The informants consisted of Sharia Supervisory Board, Developer, Assistant Branch Manager, Finance Admin, and "Rumahku Surgaku" housing consumers. Research Results: Analysis of the unbanked Islamic housing financing system involves strategies for managing late payments and default risks. Fatwa DSN MUI plays an important role as a consumer protection tool, clarifying consumer rights and obligations and creating a safe environment. Although the positive impact of Fatwa DSN MUI on consumer protection is significant, implementation of the regulation is also necessary. Non-bank Islamic housing financial institutions and related parties should be committed to ensuring the implementation of the guidelines and standards of Fatwa DSN MUI to protect consumers' interests. Conclusion: Fatwa DSN MUI plays an important role in influencing consumer protection in the non-bank Islamic housing finance system. Nonetheless, all parties involved must work together and be committed to ensuring consumer protection is properly implemented in daily practice. Keywords: financing system, bankless, risk concept